PENERAPAN USER ACCEPTANCE TEST UNTUK PERANCANGAN DAN PEMBANGUNAN SISTEM PEMESANAN OBAT STUDI KASUS PADA POLIKLINIK PRATAMA JAKARTA - Rina Novia Priyanti; Muryan Awaludin (CKI ON SPOT, 2016)
The development of the fast growing information technology needs of the times following the very need for speed and accuracy in all respects. User Acceptance Tests consist of a set of test steps, which verify if specific requirements are working for the user. If the customer and the supplier agree on the product, the software development is done. Legally. And practically. The development follows the terms of the hardware, software and in terms of human resources to operate. At this time almost all areas of life need information technology and human behavior are used to operate the application of information technology in everyday life. With computers we can manage data and data storage can be more effective and efficient. This clinic provides the drugs to be taken by Pertamina workers. Currently the process of recording reservations, purchases to suppliers as well as data recording medications taken by the patient still manually record all data recording medication to book resulting data are not neatly arranged so that it will run into difficulties when searching the necessary data. To overcome these problems, would be built applications that can be accessed only by pharmacists these applications using the programming language PHP and MySQL database. The method used is the waterfall. After testing, the application will run as a web application in Polyclinic Primary. The author hopes this application can provide convenience to Clinic Primary. Booking entitled Design of the drug to the Primary Polyclinic created using PHP and a MySQL database, builder using PHPMyAdmin, Adobe Dreamweaver. Keywords: PHP, Database Mysql, Adobe Dreamweaver